REUSE OF HUGE INDUSTRIAL AREAS - Perinkova, Martina; Kolarcikova, Lenka; Twrda, Marketa (European Scientific Journal, ESJ, 2015)
The post-industrial city of Ostrava has many brownfield blackfields and industrial areas. Gradually, these buildings and campuses governed and resolved to re-use and involvement in the function of the city. Regeneration and return them to the urban organism is very expensive and time consuming. There is a big question how to treat the polluted and debased city districts. As a successful example there is an area of National Historic Landmark called Lower Vitkovice, which has undergone over the past few years to rebirth and industrial workers were relieved visitors culture, history, sports and others. As a unique example of finding balance there is an use of technical monuments and the introduction of new life into the historic grounds of looking at the history of the complex and technical condition before reconstruction. Using qualitative analysis to evaluate the progress of our selected objects. Using principles similar objects in other post-industrial cities and their historical buildings.